Pandemi As A Reason Force Majeure In Contract Procurement Of Goods / Government Services - Fitri Yanni Dewi Siregar (NOMOI Law Review, 2020)
Procurement of goods and services is an effort to obtain the desired goods and services by doing it on the basis of logical and systematic thinking (the system of thought), following applicable norms and ethics, based on standard procurement methods and processes.However, when a pandemic event occurs, many activities of every person and institution related to the procurement of goods / services become impeded.The occurrence of the Covid-19 pandemic required the state to prioritize the safety of the population, and therefore it was necessary to provide sufficient budget.This is what causes a "budget shift" which then makes the budget for procurement of goods / services significantly reduced, or even no more.Presence of Presidential Decree No.12 of 2020concerning theDetermination of Non-Disaster Spread of Corona Virus Disease 2019 (Covid-19) was not intended to make Covid-19 as a direct reason to cancel the contract.This becomes the reason and entrance for renegotiation with the reason thatforce majeurecan certainly be based on Pasal 1244, Pasal 1245, and especially Pasal 1338 of the Civil Code.The legal effect of the presence of Presidential Decree on the Establishment of non-natural disasters Spreading Corona Virus Disease 2019 (Covid-19) against the contract goods / services procurement of government issepanjang condition offorce majeureare met,the KDP has a legitimate basis in stopping the process of selection and contracting process based on propriety and justice and the principle of budget availability.Keywords:Force Majeure,Procurement Contract.